New Andean plump toad of the genus Osornophryne (Anura: Bufonidae) from Cerro Candelaria, Ecuador - Juan P. Reyes-Puig; Miguel A. Urgiles-Merchán; H. Mauricio Ortega-Andrade; Diego F. Cisneros-Heredia; Julio C. Carrión-Olmedo; Mario H. Yáñez-Muñoz (PeerJ)
The amphibian genus Osornophryne is endemic to the northern Andes of South America and has long been considered rare. Recent explorations in the humid montane forests of the upper Pastaza Valley have uncovered previously unknown species. Here, we describe a new Andean toad species from the central Ecuadorian Andes, identified through genetic analyses and distinctive morphological and cranial traits. Osornophryne backshalli sp. nov., from Cerro Candelaria in the upper Pastaza River basin, is closely related to O. sumacoensis from Sumaco Volcano. This new species is characterized by a uniquely short fifth toe relative to toes I–III, triangular papillae on the snout tip, an occipital fold, large subconical and conical warts on the body, dorsal surfaces Brownish Olive with Spectrum Yellow and Light Neutral Gray flecks, ventral surfaces Brownish Olive with Spectrum Yellow bright blotches. Our phylogenetic analyses revise the genus taxonomy by delimiting two well-supported clades: the Osornophryne bufoniformis species group and the Osornophryne guacamayo species group. Furthermore, we show that the Pastaza River does not constitute a geographical barrier for Osornophryne distribution. These findings emphasize the value of continued exploration to expand our understanding of this genus in the humid montane forests of the Ecuadorian Andes.